1999
DOI: 10.1046/j.1432-1327.1999.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural difference in the H+,K+‐ATPase between the E1 and E2 conformations

Abstract: + were investigated by different spectroscopic approaches. No significant secondary-structure change or secondary-structure reorientation with respect to the membrane plane could be measured by attenuated total reflection Fourier transform infrared spectroscopy of oriented films. Circular dichroism and Raman spectra obtained on tubulovesicle suspensions indicated no significant secondary structure or tyrosine and tryptophan side-chain environment changes in tubulovesicle suspensions. The smallest observable st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…7). In studying the substitution of cations in ATPase, Raussens et al (52) noticed that structural changes in the protein secondary structure result in a small band shift. In addition and as shown in the deconvoluted spectrum of the protein-birnessite complex, three new bands appeared at 1641, 1619, and 1548 cm −1 (Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
“…7). In studying the substitution of cations in ATPase, Raussens et al (52) noticed that structural changes in the protein secondary structure result in a small band shift. In addition and as shown in the deconvoluted spectrum of the protein-birnessite complex, three new bands appeared at 1641, 1619, and 1548 cm −1 (Fig.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Because the hog gastric H + /K + ‐ATPase contains 1324 amino‐acid residues, a conformational change affecting 40–65 amino‐acid residues could go unnoticed with the sensitivity obtained in previous works [9]. Here, we report an ATR‐FTIR study of the gastric H + /K + ‐ATPase conformational change with a sensitivity improved by about one order of magnitude.…”
Section: Discussionmentioning
confidence: 74%
“…Many groups have attempted to determine the nature of the E1‐E2 conformational change in the P‐ATPases. Several techniques, such as CD, Raman and IR spectroscopy have been used [3,9,14–16]. While most of these studies concluded that the conformational change is small [3,9,14,16], with the notable exception of Gresalfi and Wallace [15], their sensitivity was limited to a few percent of the total signal intensity (typically 5% [9]) because of inherent limitations of the method used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Saccomani and others have suggested an increase in the a helical content upon addition of ATP, Mg 21 and K 1 [10]. Recently, Raussens and coworkers [11] were unable to observe structural changes by FTIR spectroscopy; they assumed that any changes were below the detection threshold (estimated to be 66 amino-acid residues) of the method.…”
mentioning
confidence: 97%